A method for homogenizing positive electrode material

By charging the cathode material and conductive agent during the homogenization process of the cathode material, and using ultrasonic treatment and stirring to disperse them evenly, the problem of easy agglomeration of particles is solved, and the uniformity and stability of the slurry are improved. The homogenization time is shortened and the production efficiency is improved.

CN117096259BActive Publication Date: 2025-01-21SVOLT ENERGY TECHNOLOGY CO LTD

Patent Information

Application Number
CN202311066355.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-22
Publication Date
2025-01-21
Estimated Expiration
2043-08-22

AI Technical Summary

Technical Problem

In the prior art, particles are prone to agglomeration during homogenization of the positive electrode material, resulting in poor uniformity and stability of the slurry and low production efficiency.

Method used

The first glue solution is formed by mixing the binder and the solvent, charging the positive electrode material and the conductive agent respectively, and uniformly dispersing the positive electrode material and the conductive agent using ultrasonic treatment and stirring to form a uniform positive electrode slurry.

Benefits of technology

The homogenization time is shortened, the production efficiency is improved, the particle agglomeration is reduced, and a uniform, fine, and highly stable cathode slurry is obtained, which is suitable for lithium-ion battery cathode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117096259B_ABST
    Figure CN117096259B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of homogenization of positive electrode materials for batteries, and in particular to a homogenization method for positive electrode materials. A homogenization method for positive electrode materials of the present invention comprises the following steps: S1, mixing a binder and a solvent to obtain a first glue solution; S2, respectively subjecting a positive electrode active material and a conductive agent to a charge treatment to obtain positive electrode active materials with the same charge and a conductive agent with the same charge; S3, subjecting the first glue solution, a conductive slurry and the conductive agent with the same charge to an ultrasonic treatment and a stirring treatment in sequence to obtain a second glue solution; S4, mixing the positive electrode active material with the same charge, the second glue solution and a solvent to obtain a positive electrode slurry. The homogenization method for positive electrode materials provided by the present invention improves the dispersion effect, reduces the agglomeration of particles, and can obtain a uniform and stable positive electrode slurry; and the method has simple steps, short time required, and high efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of homogenization of battery positive electrode materials, in particular to a homogenization method of positive electrode materials. Background Art

[0002] The preparation of positive electrode slurry for lithium batteries is mainly divided into two types: wet process and dry process, which includes a series of process steps such as mixing, dissolving and dispersing between liquid and liquid, liquid and solid materials, and this process is accompanied by changes in temperature, viscosity, environment, etc.

[0003] The wet homogenization process generally involves preparing a glue solution first, adding a conductive agent and a dispersant to the glue solution for dispersion, then adding the active material in batches for high-speed stirring and dispersion, and finally adding an appropriate amount of solvent to adjust the viscosity. This process has a wide range of applications, but due to the large specific surface area of ​​the conductive agent, it is easy to agglomerate, resulting in poor dispersibility, and it is easy to absorb the solvent, resulting in poor fluidity of the solvent. Even if the active material is added in batches, it is still difficult to achieve a uniformly dispersed state, which ultimately results in high fineness and high viscosity of the positive electrode slurry, long homogenization time, and low production efficiency.

[0004] The dry process is to premix the active material and conductive agent and other powder materials first, then gradually add solvents for mixing and dispersion, and finally add solvents to adjust the viscosity required for coating. This process takes a short time, but the viscosity of the prepared positive electrode slurry is low, the stability is poor, it is difficult to apply different materials, and it is easy to affect the consistency between different batches of pole pieces.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The object of the present invention is to provide a method for homogenizing positive electrode materials, which completely or partially solves the problem in the prior art that particles are easy to agglomerate during the homogenization process of positive electrode materials, resulting in poor uniformity and stability of the obtained slurry.

[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical scheme is adopted:

[0008] The present invention provides a method for homogenizing a positive electrode material, comprising the following steps:

[0009] S1, mixing the binder and the solvent to obtain a first glue solution;

[0010] S2, respectively subjecting the positive electrode material and the conductive agent to a charging treatment to obtain a positive electrode material and a conductive agent with the same charge;

[0011] S3, subjecting the first glue solution, the conductive paste and the conductive agent with the same charge to ultrasonic treatment and stirring treatment in sequence to obtain a second glue solution;

[0012] S4, mixing the positive electrode active material with the same charge, the second glue solution and the solvent to obtain a positive electrode slurry.

[0013] Furthermore, step S1 includes at least one of the following features (1) to (4);

[0014] (1) The binder comprises polyvinylidene fluoride;

[0015] (2) The solvent comprises N-methylpyrrolidone and / or nitrogen dimethyl amide;

[0016] (3) The solid content of the first glue solution is 5% to 9%;

[0017] (4) The viscosity of the first glue solution is 3000 to 5000 mPa·s.

[0018] Furthermore, in step S1, the mixing includes stirring.

[0019] Preferably, the rotational speed of the stirring treatment is 10 to 60 rpm, the rotational speed is 2500 to 4000 rpm, and the vacuum degree is less than -80 kPa; and the time of the stirring treatment is 160 to 240 min.

[0020] Further, in step S2, the positive electrode active material includes at least one of lithium iron phosphate, lithium cobalt oxide, lithium nickel cobalt manganese oxide and lithium manganese oxide;

[0021] And / or, the particle size of the positive electrode active material is 0.2 to 20 μm.

[0022] Further, step S2 includes at least one of the following features (1) to (3);

[0023] (1) The conductive agent includes conductive carbon black and / or acetylene black;

[0024] (2) The particle size of the conductive agent is 10 to 100 nm;

[0025] (3) The specific surface area of ​​the conductive agent is 40 to 130 m 2 / g.

[0026] Furthermore, in step S2, the charge-to-mass ratio of the positive electrode active material with the same charge and the conductive agent with the same charge is independently ≥ 2.4×10 -3 μC / g.

[0027] Further, in step S3, the conductive paste includes carbon nanotube conductive paste;

[0028] And / or, the solid content of the conductive paste is 2% to 8%;

[0029] Further, in step S3, the temperature of the ultrasonic treatment is 20 to 50°C, the frequency is 20 to 50kHz; the time of the ultrasonic treatment is 30 to 80min;

[0030] And / or, the rotational speed of the stirring treatment is 10 to 60 rpm, the rotational speed is 2500 to 5000 rpm, and the vacuum degree is less than -80 kPa; and the time of the stirring treatment is 20 to 40 minutes.

[0031] Furthermore, in step S4, the mixing includes stirring.

[0032] Preferably, the rotational speed of the stirring treatment is 10 to 60 rpm, the rotational speed is 2500 to 5000 rpm, and the vacuum degree is less than -80 kPa; and the time of the stirring treatment is 50 to 120 min.

[0033] Further, in step S4, the solid content of the positive electrode slurry is 65% to 70%;

[0034] And / or, the fineness of the positive electrode slurry is less than 10.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] 1. The homogenization method of the positive electrode material provided by the present invention shortens the homogenization time, improves production efficiency, reduces particle agglomeration, and improves the uniformity and stability of the slurry; at the same time, no dispersant needs to be added during the homogenization process, which is beneficial to improving the energy density of the battery.

[0037] 2. The homogenization method of the positive electrode material of the present invention requires a short time, a total time of 5 to 7 hours, and a high production efficiency; a positive electrode slurry with uniformity, fineness, high stability, a fineness of less than 10, and a viscosity of 7000 to 8000 mPa·s can be obtained, which greatly reduces the rebound of the viscosity of the positive electrode slurry.

[0038] 3. The homogenization method of the positive electrode material of the present invention has a wide range of applications and can be applied to positive electrode materials of lithium-ion batteries; especially for positive electrode slurry systems containing carbon nanotubes, the homogenization method of the present invention can improve the dispersion effect and obtain a uniform and stable positive electrode slurry. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0040] Figure 1 This is a SEM image of the positive electrode sheet after being coated with the positive electrode slurry of Example 4 of the present invention. DETAILED DESCRIPTION

[0041] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0042] A method for homogenizing a positive electrode material according to an embodiment of the present invention is described in detail below.

[0043] In some embodiments of the present invention, a method for homogenizing a positive electrode material is provided, comprising the following steps:

[0044] S1, mixing the binder and the solvent to obtain a first glue solution;

[0045] S2, respectively subjecting the positive electrode active material and the conductive agent to a charging treatment to obtain a positive electrode active material and a conductive agent with the same charge;

[0046] S3, subjecting the first glue solution, the conductive paste and the conductive agent with the same charge to ultrasonic treatment and stirring treatment in sequence to obtain a second glue solution;

[0047] S4, mixing the positive electrode active material with the same charge, the second glue solution and the solvent to obtain a positive electrode slurry.

[0048] The positive electrode material homogenization method provided by the present invention solves the problem of easy agglomeration of particles during the homogenization process; shortens the homogenization time and improves production efficiency; can obtain a uniform and stable positive electrode slurry, and does not need to add a dispersant during the homogenization process, which is beneficial to improving the energy density of the battery.

[0049] The present invention treats the positive electrode active material and the conductive agent with the same charge respectively, and utilizes the electrostatic repulsion between the charged particles to disperse the particles, thereby reducing the agglomeration of the positive electrode active material and the conductive agent; at the same time, through ultrasonic treatment, the local high temperature, high pressure, strong shock wave and micro jet generated during ultrasonic cavitation are utilized to significantly weaken the nano-action energy between the nano-particles, thereby further dispersing them; thereby shortening the homogenization time, improving the dispersion effect, and being able to obtain a uniform and stable positive electrode slurry.

[0050] In some embodiments of the present invention, the homogenization method of the positive electrode material comprises the following steps:

[0051] S1, mixing a binder and a solvent and stirring at high speed to obtain a first glue solution;

[0052] S2, subjecting the positive electrode active material to corona charging treatment through a plasma device to obtain a positive electrode active material with a positive charge; subjecting the conductive agent to corona charging treatment through a plasma device to obtain a conductive agent with a positive charge;

[0053] S3, mixing the first glue solution, the carbon nanotube conductive slurry and the conductive agent with a positive charge, and then performing ultrasonic treatment and high-speed stirring in sequence to obtain a second glue solution;

[0054] S4, after mixing the positively charged positive electrode active material and the second glue, adding a solvent and continuing to stir at a high speed to obtain a positive electrode slurry. In step S4 of the present invention, an appropriate amount of solvent is added to make the system reach a target solid content, thereby obtaining a positive electrode slurry.

[0055] The present invention adopts the steps of gelling, corona charging, ultrasonic treatment and high-speed dispersion to make the positive electrode slurry dispersed more evenly and finely, significantly reduce the probability of agglomeration, and make the slurry less viscous and more stable.

[0056] The homogenization method of the positive electrode material of the present invention has a wide range of applications, and is particularly suitable for positive electrode materials of lithium ion batteries. More importantly, for a positive electrode slurry system containing carbon nanotubes, since the carbon nanotube conductive slurry is added during the homogenization process, the homogenization becomes more difficult. The homogenization method of the present invention can improve the dispersion effect and obtain a uniform and stable positive electrode slurry.

[0057] In order to obtain a more uniform and stable positive electrode slurry, the parameters of each step in the slurrying method of the positive electrode material of the present invention are further optimized, as follows.

[0058] In some embodiments of the present invention, in step S1, the binder includes but is not limited to polyvinylidene fluoride (PVDF).

[0059] In some embodiments of the present invention, in step S1, the solvent includes N-methylpyrrolidone (NMP) and / or nitrogen dimethyl amide.

[0060] In some embodiments of the present invention, in step S1, the solid content of the first glue solution is 5% to 9%; typically but not limiting, for example, the solid content of the first glue solution can be 5%, 6%, 7%, 8%, 9% or a range of any two thereof.

[0061] In some embodiments of the present invention, in step S1, the viscosity of the first glue solution is 3000-5000 mPa·s; typically but not limitatively, for example, the viscosity of the first glue solution can be 3000 mPa·s, 3500 mPa·s, 4000 mPa·s, 4500 mPa·s, 5000 mPa·s or a range of any two thereof.

[0062] In some embodiments of the present invention, in step S1, mixing includes stirring.

[0063] In some embodiments of the present invention, in step S1, the rotational speed of the stirring treatment is 10 to 60 rpm, the rotational speed is 2500 to 4000 rpm, and the vacuum degree is <-80 kPa; typically but not restrictively, for example, the rotational speed of the stirring treatment can be 2500 rpm, 3000 rpm, 3500 rpm, 4000 rpm or a range of any two thereof.

[0064] In some embodiments of the present invention, in step S1, the stirring treatment time is 160 to 240 minutes; typically but not limitatively, for example, the stirring treatment time can be 160 minutes, 180 minutes, 200 minutes, 220 minutes, 240 minutes or a range of any two thereof.

[0065] In some embodiments of the present invention, in step S2, the positive electrode active material includes at least one of lithium iron phosphate, lithium cobalt oxide, lithium nickel cobalt manganese oxide and lithium manganese oxide.

[0066] In some embodiments of the present invention, in step S2, the particle size of the positive electrode active material is 0.2 to 20 μm; typically but not limitatively, for example, the particle size of the positive electrode active material is 0.2 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 5 μm, 7 μm, 10 μm, 13 μm, 15 μm, 17 μm, 20 μm or a range consisting of any two of them.

[0067] In some embodiments of the present invention, in step S2, the conductive agent includes conductive carbon black (Super-P) and / or acetylene black; the conductive agent in step S2 is in the form of solid powder.

[0068] In some embodiments of the present invention, in step S2, the particle size of the conductive agent is 10 to 100 nm; typically but not limitatively, for example, the particle size of the conductive agent can be 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm or a range of any two thereof.

[0069] In some embodiments of the present invention, in step S2, the specific surface area of ​​the conductive agent is 40 to 130 m 2 / g; typically but not limiting, for example, the specific surface area of ​​the conductive agent can be 40m 2 / g, 50m 2 / g, 60m 2 / g, 70m 2 / g, 80m 2 / g, 90m 2 / g、100m 2 / g, 110m 2 / g, 120m 2 / g, 130m 2 / g or a range consisting of any two of them.

[0070] In some embodiments of the present invention, in step S2, the charging treatment includes performing corona charging treatment by a plasma device.

[0071] In some embodiments of the present invention, in step S2, the charge-to-mass ratio of the positive electrode active material with the same charge and the conductive agent with the same charge are independently ≥ 2.4×10 -3 μC / g; the charge-to-mass ratio of the positive electrode active material with the same charge Q / M≥2.4×10 -3 μC / g; the charge-to-mass ratio of conductive agents with the same charge Q / M≥2.4×10 -3 μC / g; wherein Q is the charge of the positive electrode active material with the same charge or the conductive agent with the same charge, and M is the mass of the positive electrode active material with the same charge or the conductive agent with the same charge.

[0072] In some specific embodiments of the present invention, the charge-to-mass ratio of the positive electrode active material with the same charge is 3.5×10 -3 μC / g~4.5×10 -3 μC / g; the charge-to-mass ratio of the conductive agent with the same charge is 5.5×10 -3 μC / g~6.5×10 -3 μC / g.

[0073] In some embodiments of the present invention, in step S3, the conductive paste includes carbon nanotube conductive paste; preferably, the conductive paste is obtained by mixing carbon nanotubes and N-methylpyrrolidone.

[0074] In some embodiments of the present invention, in step S3, the solid content of the conductive paste is 2% to 8%; typically but not limiting, for example, the solid content of the conductive paste can be 2%, 3%, 4%, 5%, 6%, 7%, 8% or a range of any two thereof.

[0075] In some embodiments of the present invention, in step S3, the mass ratio of the binder, the conductive paste, and the conductive agent with the same charge in the first glue solution is 2:1:1.

[0076] In some embodiments of the present invention, in step S3, the temperature of ultrasonic treatment is 20-50°C; typically but not limiting, for example, the temperature of ultrasonic treatment can be 20°C, 30°C, 40°C, 50°C or a range of any two thereof; preferably 40-50°C.

[0077] The present invention adopts a suitable temperature for ultrasonic treatment, which is beneficial to further dispersion of particles; as the temperature increases, the dispersion of particles can be promoted, but as the temperature increases, the probability of particle collision increases, which may lead to agglomeration of particles.

[0078] In some embodiments of the present invention, in step S3, the frequency of ultrasonic treatment is 20 to 50 kHz; typically but not limiting, for example, the frequency of ultrasonic treatment can be 20 kHz, 30 kHz, 40 kHz, 50 kHz or a range of any two thereof.

[0079] In some embodiments of the present invention, in step S3, the ultrasonic treatment time is 30 to 80 min; typically but not limiting, for example, the ultrasonic treatment time can be 30 min, 40 min, 50 min, 60 min, 70 min, 80 min or a range of any two thereof.

[0080] In some embodiments of the present invention, in step S3, the rotational speed of the stirring treatment is 10 to 60 rpm, the rotational speed is 2500 to 5000 rpm, and the vacuum degree is <-80 kPa; typically but not limitatively, for example, the rotational speed of the stirring treatment can be 2500 rpm, 3000 rpm, 3500 rpm, 4000 rpm, 4500 rpm, 5000 rpm or a range of any two thereof.

[0081] In the present invention, if the stirring rate is too fast, the PVDF molecular chain will be broken and the PVDF will be ineffective, which will cause the viscosity of the slurry to drop sharply and coating will not be possible.

[0082] In some embodiments of the present invention, in step S3, the stirring treatment time is 20 to 40 minutes; typically but not limiting, for example, the stirring treatment time can be 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes or a range of any two thereof.

[0083] In some embodiments of the present invention, in step S4, the solvent includes N-methylpyrrolidone and / or nitrogen dimethylamide.

[0084] In some embodiments of the present invention, in step S4, the mass ratio of the positive electrode active material with the same charge to the binder in the second glue solution is 96:2.

[0085] In some embodiments of the present invention, in step S4, mixing includes stirring.

[0086] In some embodiments of the present invention, in step S4, the revolution speed of the stirring treatment is 10-60rpm, the rotation speed is 2500-5000rpm, and the vacuum degree is <-80kPa; typically but not limitatively, for example, the rotation rate of the stirring treatment can be 2500rpm, 300rpm, 3500rpm, 4000rpm, 4500rpm, 5000rpm or a range of any two thereof.

[0087] In some embodiments of the present invention, in step S4, the stirring treatment time is 50 to 120 min; typically but not limitatively, for example, the stirring treatment time can be 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min or a range value consisting of any two of them.

[0088] In some embodiments of the present invention, the solid content of the positive electrode slurry is 65% to 70%, and the fineness is <10; typically but not limiting, for example, the solid content of the positive electrode slurry can be 65%, 66%, 67%, 68%, 69%, 70% or a range of any two thereof.

[0089] In some embodiments of the present invention, the fineness of the positive electrode slurry is ≤5.

[0090] In some embodiments of the present invention, the viscosity of the positive electrode slurry is 7000-8000 mPa·s; typically but not limitatively, for example, the viscosity of the positive electrode slurry can be 7000 mPa·s, 7100 mPa·s, 7200 mPa·s, 7300 mPa·s, 7400 mPa·s, 7500 mPa·s, 7600 mPa·s, 7700 mPa·s, 7800 mPa·s, 7900 mPa·s, 8000 mPa·s or a range of any two thereof.

[0091] In some embodiments of the present invention, the total time of the homogenization process of the positive electrode material is 5 to 7 hours.

[0092] By adopting the positive electrode material homogenization method of the present invention, a positive electrode slurry with uniformity, good stability and a viscosity of 7000-8000 mPa·s can be obtained, and the rebound of the viscosity of the positive electrode slurry is greatly reduced.

[0093] Example 1

[0094] The method for homogenizing the positive electrode material provided in this embodiment comprises the following steps:

[0095] S1, adding PVDF into NMP and stirring at high speed, stirring at a rotational speed of 15 rpm and a rotational speed of 3000 rpm for 200 min, to obtain a first glue solution with a solid content of 7% and a viscosity of 4200 mPa·s;

[0096] S2, respectively, lithium iron phosphate with a particle size of 0.3 to 6 μm and lithium iron phosphate with a particle size of 20 to 60 nm and a specific surface area of ​​45 to 80 m 2 / g Super-P was treated with corona charging by plasma equipment to obtain a charge-to-mass ratio of 4.0×10 -3 μC / g of positively charged lithium iron phosphate and a charge-to-mass ratio of 6.0×10 -3 μC / g of positively charged Super-P;

[0097] S3, according to the mass ratio of PVDF, carbon nanotube conductive paste and positively charged Super-P being 2:1:1, the first glue solution and carbon nanotube conductive paste are added to the positively charged Super-P for ultrasonic treatment, the temperature of ultrasonic treatment is 40°C and the frequency is 20kHz, and after ultrasonic treatment for 70 minutes, high-speed stirring is performed at a speed of 40 rpm and a rotational speed of 3000 rpm for 30 minutes to obtain a second glue solution; wherein, the carbon nanotube conductive paste is obtained by mixing carbon nanotubes and NMP, and the solid content is 4%;

[0098] S4. According to the mass ratio of positively charged lithium iron phosphate and PVDF being 96:2, the positively charged lithium iron phosphate is added to the second gel solution, and then NMP is added for high-speed stirring at a rotational speed of 20 rpm and a rotational speed of 3000 rpm for 100 minutes to obtain a positive electrode slurry with a solid content of 68%.

[0099] Example 2

[0100] The method for homogenizing the positive electrode material provided in this embodiment comprises the following steps:

[0101] S1, adding PVDF into NMP and stirring at high speed, stirring at a rotational speed of 20 rpm and a rotational speed of 4000 rpm for 180 min, to obtain a first glue solution with a solid content of 7% and a viscosity of 3670 mPa·s;

[0102] S2, respectively, lithium iron phosphate with a particle size of 0.3 to 6 μm and lithium iron phosphate with a particle size of 20 to 60 nm and a specific surface area of ​​45 to 80 m 2 / g Super-P was treated with corona charging by plasma equipment to obtain a charge-to-mass ratio of 4.0×10 -3 μC / g of positively charged lithium iron phosphate and a charge-to-mass ratio of 6.0×10 -3 μC / g of positively charged Super-P;

[0103] S3, according to the mass ratio of PVDF, carbon nanotube conductive paste and positively charged Super-P being 2:1:1, the first glue solution and carbon nanotube conductive paste are added to the positively charged Super-P for ultrasonic treatment, the temperature of ultrasonic treatment is 40°C and the frequency is 30kHz, and after ultrasonic treatment for 30 minutes, high-speed stirring is performed at a speed of 40 rpm and a rotational speed of 3000 rpm for 30 minutes to obtain a second glue solution; wherein, the carbon nanotube conductive paste is obtained by mixing carbon nanotubes and NMP, and the solid content is 4%;

[0104] S4. According to the mass ratio of positively charged lithium iron phosphate and PVDF being 96:2, the positively charged lithium iron phosphate is added to the second gel solution, and then NMP is added for high-speed stirring at a rotational speed of 20 rpm and a rotational speed of 3000 rpm for 100 minutes to obtain a positive electrode slurry with a solid content of 68%.

[0105] Example 3

[0106] The method for homogenizing the positive electrode material provided in this embodiment comprises the following steps:

[0107] S1, adding PVDF into NMP and stirring at high speed, stirring at a rotational speed of 20 rpm and a rotational speed of 4000 rpm for 180 min, to obtain a first glue solution with a solid content of 7% and a viscosity of 3670 mPa·s;

[0108] S2, respectively, lithium iron phosphate with a particle size of 0.3 to 6 μm and lithium iron phosphate with a particle size of 30 to 50 nm and a specific surface area of ​​50 to 80 m 2 / g of acetylene black was treated with corona charging by plasma equipment to obtain a charge-to-mass ratio of 4.0×10 -3 μC / g of positively charged lithium iron phosphate and a charge-to-mass ratio of 6.0×10 -3 μC / g of positively charged acetylene black;

[0109] S3, according to the mass ratio of PVDF, carbon nanotube conductive paste and positively charged acetylene black being 2:1:1, the first glue and carbon nanotube conductive paste are added to the positively charged acetylene black for ultrasonic treatment, the temperature of ultrasonic treatment is 40°C and the frequency is 35kHz, and after ultrasonic treatment for 40 minutes, high-speed stirring is performed at a speed of 40 rpm and a rotational speed of 3000 rpm for 30 minutes to obtain a second glue; wherein the carbon nanotube conductive paste is obtained by mixing carbon nanotubes and NMP, and the solid content is 4%;

[0110] S4. According to the mass ratio of positively charged lithium iron phosphate and PVDF being 96:2, the positively charged lithium iron phosphate is added to the second gel solution, and then NMP is added for high-speed stirring at a rotational speed of 35 rpm and a rotational speed of 4000 rpm for 50 minutes to obtain a positive electrode slurry with a solid content of 68%.

[0111] Example 4

[0112] The homogenization method of the positive electrode material provided in this embodiment refers to that in Embodiment 3, except that in step S4, the rotation speed is 5000 rpm.

[0113] Example 5

[0114] The homogenization method of the positive electrode material provided in this embodiment refers to that in Embodiment 1, except that in step S4, the rotation speed is 4000 rpm.

[0115] Example 6

[0116] The homogenization method of the positive electrode material provided in this embodiment refers to Example 3, with the only difference being that in step S3, the temperature of the ultrasonic treatment is 60°C and the stirring speed is 2000 rpm; in step S4, the stirring speed is 2000 rpm.

[0117] Comparative Example 1

[0118] The homogenization method of the positive electrode material provided in this comparative example refers to Example 1, with the only difference being that in step S3, the first colloid and the carbon nanotube conductive slurry are added to the positively charged Super-P and stirred at high speed at a rotational speed of 40 rpm and a rotational speed of 3000 rpm for 100 min to obtain a second colloid.

[0119] Comparative Example 2

[0120] The method for homogenizing the positive electrode material provided in this comparative example comprises the following steps:

[0121] S1, adding PVDF into NMP and stirring at high speed, stirring at a rotational speed of 20 rpm and a rotational speed of 4000 rpm for 180 min, to obtain a first glue solution with a solid content of 7% and a viscosity of 3670 mPa·s;

[0122] S2, lithium iron phosphate with a particle size of 0.3 to 6 μm and lithium iron phosphate with a particle size of 30 to 50 nm and a specific surface area of ​​50 to 80 m 2 / g of acetylene black was mixed and corona charged by plasma equipment to obtain a charge-to-mass ratio of 6.0×10 -3 μC / g of positively charged mixture;

[0123] S3. According to the mass ratio of PVDF, carbon nanotube conductive slurry and positively charged mixture of 2:1:97, the first glue and carbon nanotube conductive slurry are added to the positively charged mixture for ultrasonic treatment. The temperature of ultrasonic treatment is 40°C and the frequency is 35kHz. After ultrasonic treatment for 40 minutes, NMP is added for high-speed stirring. The stirring is carried out at a speed of 40 rpm and a rotational speed of 3000 rpm for 80 minutes to obtain a positive electrode slurry with a solid content of 68%; wherein, the carbon nanotube conductive slurry is obtained by mixing carbon nanotubes and NMP, and the solid content is 4%.

[0124] Test Example 1

[0125] The viscosity and fineness of the positive electrode slurries prepared in Examples 1 to 6 and Comparative Examples 1 to 2 were tested, and the results are shown in Table 1.

[0126] Among them, the viscosity testing method is: install the viscometer so that the horizontal bubble of the body is placed in the black circle, immerse the rotor in the positive electrode slurry to the groove mark on the rotor rod, click start, and read the viscosity value after the viscosity indication stabilizes.

[0127] The test method for fineness is: use alcohol to wash and soak the scraper and bottom, take a spoonful of positive electrode slurry and place it on the scraper fineness meter, place the scraper horizontally on the upper end of the scraper fineness meter, make the scraper perpendicular to the surface of the scraper fineness meter, pull the scraper from the deep part of the groove to the shallow part at an appropriate speed, and read the scale value where the particles are evenly exposed in the groove. The reading value is the fineness of the measured object.

[0128] Table 1

[0129]

[0130]

[0131] The positive electrode slurry prepared in Example 4 was coated on the surface of the current collector to obtain a positive electrode sheet, which was subjected to a scanning electron microscope test. The results are as follows: Figure 1 shown.

[0132] from Figure 1 It can be seen that the electrode sheet particles prepared by the positive electrode slurry obtained by the positive electrode material homogenization method of the present invention are well dispersed, and there is no abnormal agglomeration of the conductive agent particles.

[0133] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for homogenizing a positive electrode material, characterized in that: The steps include: S1. Mixing a binder and a solvent to obtain a first glue solution; the solid content of the first glue solution is 5% to 9%, and the viscosity of the first glue solution is 3000 to 5000 mPa·s; S2, subjecting the positive electrode active material to corona charging treatment through a plasma device to obtain a positive electrode active material with a positive charge; subjecting the conductive agent to corona charging treatment through a plasma device to obtain a conductive agent with a positive charge; The conductive agent includes conductive carbon black and / or acetylene black; The charge-to-mass ratio of the positive electrode active material with positive charge and the positive conductive agent with positive charge is independently ≥ 2.4×10 -3 μC / g; S3, subjecting the first glue solution, the conductive paste and the conductive agent with a positive charge to ultrasonic treatment and stirring treatment in sequence to obtain a second glue solution; The conductive paste includes carbon nanotube conductive paste; The solid content of the conductive paste is 2% to 8%; The temperature of the ultrasonic treatment is 20-50°C, the frequency is 20-50kHz; the time of the ultrasonic treatment is 30-80min; S4, mixing the positively charged positive electrode active material, the second glue solution and the solvent to obtain a positive electrode slurry; The solid content of the positive electrode slurry is 65% to 70%; The fineness of the positive electrode slurry is less than 10; The viscosity of the positive electrode slurry is 7000-8000 mPa·s.

2. The method for homogenizing the positive electrode material according to claim 1, characterized in that: In step S1, the binder includes polyvinylidene fluoride; And / or, the solvent comprises N-methylpyrrolidone and / or nitrogen dimethylamide.

3. The method for homogenizing the positive electrode material according to claim 1, characterized in that: In step S1, the mixing includes stirring.

4. The method for homogenizing the positive electrode material according to claim 3, characterized in that: In step S1, the rotational speed of the stirring treatment is 10-60 rpm, the rotational speed is 2500-4000 rpm, and the vacuum degree is less than -80 kPa; and the time of the stirring treatment is 160-240 min.

5. The method for homogenizing the positive electrode material according to claim 1, characterized in that: In step S2, the positive electrode active material includes at least one of lithium iron phosphate, lithium cobalt oxide, lithium nickel cobalt manganese oxide and lithium manganese oxide; And / or, the particle size of the positive electrode active material is 0.2-20 μm.

6. The method for homogenizing the positive electrode material according to claim 1, characterized in that: In step S2, the particle size of the conductive agent is 10-100 nm; And / or, the specific surface area of ​​the conductive agent is 40-130 m 2 / g.

7. The method for homogenizing the positive electrode material according to claim 1, characterized in that: In step S3, the rotational speed of the stirring treatment is 10-60 rpm, the rotational speed is 2500-5000 rpm, and the vacuum degree is less than -80 kPa; and the time of the stirring treatment is 20-40 min.

8. The method for homogenizing the positive electrode material according to claim 1, characterized in that: In step S4, the mixing includes stirring.

9. The method for homogenizing the positive electrode material according to claim 8, characterized in that: In step S4, the rotational speed of the stirring treatment is 10-60 rpm, the rotational speed is 2500-5000 rpm, and the vacuum degree is less than -80 kPa; and the time of the stirring treatment is 50-120 min.

Citation Information

Patent Citations

  • Homogenating method of lithium battery positive electrode slurry

    CN109745881A

  • Battery slurry stirring method

    CN112701241A

Cited By

  • Homogenization method for positive electrode material

    EP4765210A1